The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1080/03009730802688819
|View full text |Cite
|
Sign up to set email alerts
|

Supratrochlear foramen of the humerus: An anatomico-radiological study with clinical implications

Abstract: BackgroundThe supratrochlear foramen (STF) of the humerus has been a neglected entity in standard anatomy and orthopaedics text-books. The knowledge of the presence of STF in a humerus may be important for preoperative planning for treatment of supracondylar fractures. The presence of STF may also result in erroneous interpretation of radiographs.MethodsThe STF was studied in detail in 384 (220 left side and 164 right side) human dried humeri of unknown sex and age. The topographical anatomy of the STF was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
49
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 12 publications
(15 reference statements)
15
49
5
2
Order By: Relevance
“…This result was consistent with earlier reports (12,13,16), although it was different from the result found by Nayak and Das (22), who found that the STF was more common on the right. Recent studies by Ndou et al (24) and Mahajan et al (25) showed an incidence of STF in 32.5% and 26% of the humeri, respectively.…”
Section: Causes Of the Stfcontrasting
confidence: 35%
“…This result was consistent with earlier reports (12,13,16), although it was different from the result found by Nayak and Das (22), who found that the STF was more common on the right. Recent studies by Ndou et al (24) and Mahajan et al (25) showed an incidence of STF in 32.5% and 26% of the humeri, respectively.…”
Section: Causes Of the Stfcontrasting
confidence: 35%
“…Diwan et al [9] have shown similar frequencies of septal aperture in both sexes. There are studies where the dominance of the right humerus in septal aperture frequency has been observed [28,39]; and there are also studies where the similar incidence of septal aperture on both sides has been observed [39].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with this trait may be able to overextend the elbow joint [8]. The frequency of the foramen among mankind ranges from about 0.3% to 60%, in different races [for the details see 18,28,34,35,39]. The cause of septal aperture has been widely discussed; however, the problem has not been solved yet.…”
Section: Introductionmentioning
confidence: 99%
“…Number of hypothesis were proposed regarding the cause of supratrochlearforamen.Some opine that it may be a racial anomaly or atavistic 7 . Darwin mentioned STF in humans as one of the characteristic that shows man's close relationship to lower forms 8 .According to Hirsh, the thin plate of bone is always present between olecranon and coronoid fossa upto 7 years after which the bony plate occasionally becomes absorbed to form the STF 9 .Mays suggested that the perforation is the result of hyperflexion of elbow joint which resorbs the humeral septum when the coronoid process of ulna make contact with it 10 . The global statistics shows an incidence of 4.2% in White Americans, 18.4% in American Negroes , 8.8% in Germans , 18.1% in Japanese, 21.7% in African Negroes, 43.9% in Egyptians and 9.4% in Italian populations .Theincidence is alsodifferent in different parts of Indian population, 27.4% in Eastern Indians,32% in Central Indians,27.5%in North Indians and 28% in South Indians 11 .…”
Section: Discussionmentioning
confidence: 99%